1994
DOI: 10.1096/fasebj.8.1.8299889
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of glucose transporters by glucose: a review of studies in vivo and in cell cultures

Abstract: Glucose transporters are membrane-embedded proteins that mediate the uptake of glucose from the surrounding medium into the cell. Glucose is the main fuel for most cells, and its uptake is rate-limiting for glucose utilization. For this reason, it is expected that glucose transport is tightly regulated. Whereas rapid regulation of glucose transporters by hormones has been known for some time, the regulation of glucose transporters by substrate availability (i.e., by glucose itself) is less well understood. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
160
0
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(175 citation statements)
references
References 51 publications
10
160
0
5
Order By: Relevance
“…Results from our [1-5, 20, 21] and other laboratories [9] over recent years convincingly demonstrated that extracellular glucose is an important feed-back regulator of its transport through the cell membrane. Glucose transport in skeletal muscle is the limiting step for hexose metabolism in toto, therefore regulation of this step by glucose can be expected to result in the modulation of all aspects of cellular glucose metabolism.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Results from our [1-5, 20, 21] and other laboratories [9] over recent years convincingly demonstrated that extracellular glucose is an important feed-back regulator of its transport through the cell membrane. Glucose transport in skeletal muscle is the limiting step for hexose metabolism in toto, therefore regulation of this step by glucose can be expected to result in the modulation of all aspects of cellular glucose metabolism.…”
Section: Discussionmentioning
confidence: 77%
“…Glucose has been shown to regulate the expression and steady-state level of GLUT1 mRNA in several types of cells [9]. We have shown before that glucose reduces the content of GLUT1 mRNA in L8 myocytes in a dose-and time-dependent manner [5].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the postabsorptive state, insulin action in muscle and adipose tissue results in increased glucose uptake from the circulation, thereby maintaining plasma euglycemia and preventing hyperglycemia (1)(2)(3). Defects in this pathway result in insulin resistance, a condition in which excessive concentrations of insulin are required to reduce blood glucose levels and often precede the development of frank Type II diabetes (3,4).…”
mentioning
confidence: 99%